EVALUASI LAYANAN BIMBINGAN KELOMPOK DI SEKOLAH MENEGAH PERTAMA BERDASARKAN MODEL KESENJANGAN (DISCREPANCY MODEL) - Dian Ari Widyastuti (JURNAL KONSELING GUSJIGANG, 2017)
This study aims to evaluate the implementation of group guidance services at one of “SMP Negeri” in Madiun District.. This research belongs to discrepancy model of evaluation research using mixed method. The research subjects were four counselors at one of “SMP Negeri” in Madiun District. The research instrument used questionnaires of group guidance services as well as interview guides for counselors and students. Technical data analysis using descriptive statistical analysis and triangulation. Evaluation results indicate that the implementation of group guidance services at one of “SMP Negeri” in Madiun District included in good enough category. It is suggested for counselor to improve the quality of group guidance services in order to assist the optimal development of students.